Effect of ammonium sulphate as a precursor for the synthesis of glucosamine from coconut sap - Ika Atsari Dewi; Aby Dea Admir; Hendrix Yulis Setyawan; Nur Lailatul Rahmah; Elya Mufidah (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2022)
Glucosamine is useful for overcoming joint disease or osteoarthritis. Glucosamine can be produced through synthesis involving carbon and amine. Carbon can come from plant derivatives that contain sugar, like coconut sap. While the amine branch can be derived from ammonium sulphate. This study aims to determine the effect of ammonium sulphate added as a precursor in the process of synthesizing glucosamine from coconut sap towards physiochemical characteristics of glucosamine. The research used a one-factor-randomized design with addition of six levels of ammonium sulphate, that are 1,5 M; 2M; 2,5 M; 3 M; 3,5 M and 4 M. The characterisation includes the glucosamine concentration, pH, solubility, colour, and loss on drying (LOD). The best treatment was selected by using the TOPSIS method. The results showed that the best treatment was the addition of a 3.5 M ammonium sulphate precursor compound which had a glucosamine content of 801.67 ppm; yield of 1.603%; pH 4.79; and LOD of 0.837%. The precursor concentration had significant effects on the yield of glucosamine synthesised from coconut sap. The higher of glucosamine content and the resulting yield indicate the efficiency of the treatment applied to the sample is higher.